Snow cover on the Lagonaky high plateau (Western Caucasus) - Yu. V. Efremov; A. V. Zimnitskiy (Лëд и снег, 2017)
The paper presents characteristics of a snow cover observed on the Lagonaky high plateau (the Western Caucasus) in the interfluve of the rivers Belaya and Pshekha along two snow-measuring courses. The period of observations is 1973–2015, and the altitude interval is 460–2020 m. The characteristics measured are the following: depths of snow cover, the snow density, and temperature of different snow layers in the test pits. The stratigraphy of the snow thickness is described. In different years, observations did show changes in the depths which felt within a wide range of values from a few centimeters up to 5–6 m at the same points. The observations allowed determination of dates of snow appearance (setting-up of snow cover) as well as the disappearance in different parts of the Lagonaky high plateau. Durations of the snow cover in different altitudinal belts were also determined. By the end of March the snow cover disappears to altitudes of 700 m, and after 20th of April the slopes become free of snow to 1000 m. The snow cover duration in the low-altitude zone (500–1000 m) is 70–80 days, while in the middle altitudes (1,000–1,500 m) it is 130 days. In the highlands (above 2000 m), the snow cover lasts for 215 days. It must be emphasized that during the last five years the duration of snow cover has changed significantly. Materials of snow surveys showed that snow depths and water contents (water equivalents of snow cover) significantly differ from year to year. In seasons 1975/76, 1978/79, 19861/87, 1989/90 the winters were extremely snowy, while winters in 1976/77, 1979/80, 1983/84, 1990/91, 2013–2015 had small amount of snow. According to data of distant snow-measuring sticks, the maximum values of the snow depth (610 cm) have been recorded in March of 1976 near the tourist shelter Fisht (1596 м). Significant changes in the distribution of snow cover in recent years were probably related to the global climate changes.